2018
DOI: 10.1186/s12920-018-0354-x
|View full text |Cite
|
Sign up to set email alerts
|

HLA and proteasome expression body map

Abstract: BackgroundThe presentation of HLA peptide complexes to T cells is a highly regulated and tissue specific process involving multiple transcriptionally controlled cellular components. The extensive polymorphism of HLA genes and the complex composition of the proteasome make it difficult to map their expression profiles across tissues.MethodsHere we applied a tailored gene quantification pipeline to 4323 publicly available RNA-Seq datasets representing 55 normal tissues and cell types to examine expression profil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
76
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(93 citation statements)
references
References 60 publications
9
76
0
2
Order By: Relevance
“…For example, for the GEUVADIS original quantifications, HLA-B is twice as expressed as HLA-A, and HLA-DPA1 is more expressed than HLA-DRB1 ( Figure S1). Our results are more in accordance with previous HLA-personalized approaches which shows, for example, that HLA-DR is always more expressed than HLA-DP and HLA-DQ [32]. We found that, although the expression estimates using the reference transcriptome were usually lower than using the personalized index, the correlation between indices was greater than 0.87 for every locus except for HLA-DQA1 ( Figure 4).…”
Section: Analysis Of the Geuvadis Datasetsupporting
confidence: 91%
See 1 more Smart Citation
“…For example, for the GEUVADIS original quantifications, HLA-B is twice as expressed as HLA-A, and HLA-DPA1 is more expressed than HLA-DRB1 ( Figure S1). Our results are more in accordance with previous HLA-personalized approaches which shows, for example, that HLA-DR is always more expressed than HLA-DP and HLA-DQ [32]. We found that, although the expression estimates using the reference transcriptome were usually lower than using the personalized index, the correlation between indices was greater than 0.87 for every locus except for HLA-DQA1 ( Figure 4).…”
Section: Analysis Of the Geuvadis Datasetsupporting
confidence: 91%
“…A strategy to overcome these challenges is the mapping of reads to an HLA-personalized reference, rather than to a single reference genome. For example, seq2HLA is a tool developed by [30] to provide in-silico HLA types and expression estimates, and later applied to demonstrate that different tumors types are associated with different HLA expression levels [31], and also to provide a large catalog of HLA expression in 56 human tissues and cell types [32]. AltHapAlignR [33] is another recently described algorithm which infers the MHC references which are the closest to the individual's MHC haplotypes, and maps reads to them.…”
Section: Introductionmentioning
confidence: 99%
“…We demonstrate that HLA genes present cell-type specific expression (Boegel et al 2018) and that HLA loss of expression can be evaluated per-cell and per-cluster. Using five AML samples published in (Petti et al 2019) for which HLA class I and class II genotypes were provided by the authors, we demonstrate the ability to find cell type specific allele bias when cell types have been annotated using marker genes.…”
Section: Resultsmentioning
confidence: 94%
“…Due to the nature of 3’ GEX data, nearly all reads are sequenced from the opposite end of the HLA-A transcript from the variable sites used to define HLA types S1. These variable sites are mostly located in exons 2 and 3, while the 3’ end of the transcripts are mostly homologous between the class I genes Boegel et al 2018. As a result of the coverage distribution of 3’ GEX data, very few HLA-A molecules could be assigned to an allele.…”
Section: Resultsmentioning
confidence: 99%
“…In transplant practices, the importance of RNA or protein expression levels of HLA genes have been gradually realized. There are some reports on HLA typing using RNA-seq data and quantification of HLA genes as well [18][19][20][21]. However, to date, few reports have been available on the HLA typing at the singlecell level by using scRNA-seq data.…”
Section: Introductionmentioning
confidence: 99%